Graphene boosted Cu2GeS3 for advanced lithium-ion batteries. Issue 3 (23rd January 2017) - Fu, Lin; Zhang, Chuanjian; Chen, Bingbing; Zhang, Zhonghua; Wang, Xiaogang; Zhao, Jingwen; He, Jianjiang; Du, Huiping; Cui, Guanglei
Abstract : Ternary Cu2 GeS3 (CGS) serves as lithium ion battery anode materials for the first time, whose electrochemical performance is significantly improved by the introduction of reduced graphene oxide. Abstract : Germanium-based materials as the anode for lithium ion batteries (LIBs) have been investigated extensively because of their high theoretical capacities. However, ternary germanium-based sulfides as the anode material for LIBs have been rarely investigated until now. In this work, we successfully synthesized a novel ternary Cu2 GeS3 (CGS) incorporated with reduced graphene oxide (CGS@RGO) and measured their lithium storage performance. As a result, the binder-free CGS@RGO anodes deliver excellent stable cycling properties and high rate capabilities. These improved properties can be ascribed to the introduction of RGO, which acts as a buffer to accommodate the large volume change and maintain the structural integrity of the electrode. More importantly, this work opens an opportunity to develop novel Ge-based anodes for high performance LIBs.